2011
DOI: 10.1136/aim.2011.004085
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Hot Flushes in Perimenopausal and Postmenopausal Women: A Randomised, Sham-Controlled Trial

Abstract: Objectives To determine the effect of acupuncture in treating hot fl ushes in perimenopausal or postmenopausal women. Methods The study was a randomised single-blind sham-controlled clinical trial. Perimenopausal or postmenopausal women with moderate or severe hot fl ushes were randomised to receive real or sham acupuncture. Both groups underwent a 4-week run-in period before the treatment. The real acupuncture group received 11 acupuncture treatments for 7 weeks, and the control group underwent sham acupunctu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…Previous RCTs show acupuncture in the treatment of symptoms of both perimenopausal and postmenopausal females has no advantage, compared with placebo needles [16-19]. Compared with no medical treatment (for example, self-caring, waiting), however, acupuncture is able to relieve symptoms quite well [16,17,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous RCTs show acupuncture in the treatment of symptoms of both perimenopausal and postmenopausal females has no advantage, compared with placebo needles [16-19]. Compared with no medical treatment (for example, self-caring, waiting), however, acupuncture is able to relieve symptoms quite well [16,17,29].…”
Section: Discussionmentioning
confidence: 99%
“…However, several randomized controlled trials (RCTs) indicated that acupuncture is not superior to sham acupuncture in relieving perimenopausal symptoms [16-19]. Reliable and valid evidence for the effectiveness of treating perimenopausal syndrome with acupuncture is still inadequate, due to the number, size, design scheme, and quality of recent studies.…”
Section: Introductionmentioning
confidence: 99%
“…All patients were treated at least 2 times per week in the first month. Most of the study participants had a treating period of 8-12 weeks, except for 1 participant [9], whose treatment lasted only 4 weeks. For this analysis, a random-effects model was used due to the large amount of heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…Management not using acupuncture. 4. The design of the study did not include acupuncture and control groups.…”
Section: Exclusion Criteriamentioning
confidence: 99%